Delivery of technical information to smallholder dairy farmers in Kiambu District - Wambugu, M.; Wahome, R.G.; Gachuiri, C.; Kaitho, R.; Omore, Amos O.; Tanner, J.C. (International Livestock Research Institute, 1998)
A survey was conducted to determine the sources and delivery of technical information to smallholder dairy farmers in Kiambu District. Sixty-three farmers in three wealth groups (rich, medium, poor) of 21 farmers each from three different locations, were selected at random from maps drawn by communities. A structured questionnaire was administered to collect information on farmers’ level of exposure to different dairy information sources and their involvement in extension activities during 1997. Preliminary results indicate that most poor farmers (66%) relied on neighbors as their primary information source. Field days run by dairy cooperative societies were the most important organized information delivery channel for poor (28%) and medium (38%) farmers. Private and co-operative veterinary services concentrated on rich farms with 33% of these households having contact compared with only 14% of poor households. The government veterinary or livestock services contacted less than 20% of households either in farm visits or field days. Besides visits by private veterinary officers to wealthy farmers the frequency of contact with livestock professionals was therefore limited for all communities. Preliminary conclusions are that for Kiambu, which has a well established smallholder dairy industry, group meetings organized by cooperatives are more likely to reach the poorer sectors of the community. This coupled with frequent neighbour-to-neighbour discussions may currently be the most effective dairy information delivery channel.